Emerging Evidence for Association of Transsulfuration Pathway with Hypoxia Responses - Jain, Neha; Sharma, Manish (Defence Life Science Journal, 2024)
When people ascend to a high altitude (HA), the body’s oxygen (O2) sensing mechanisms can sense perturbation in partial pressure and trigger adaptive responses. Rapid ascending to HA without ample time for acclimatization culminates in high-altitude illnesses, which can derail the body functioning of lowlanders moving to HA. High-altitude native populations have undergone positive natural selection to efficiently overcome the challenges of chronic hypobaric hypoxia (HH) and thus offer a unique model to understand physiological and genetic adaptations at high altitudes. In addition, evolutionary shreds of evidence propose that sulfur belonging to the same periodic table family can mimic oxygen to bypass its metabolic oxygen demand and modulate energy production.Intriguingly, our group has identified a strong association between diminished hydrogen sulfide (H2S)levels and HH-induced pathological responses. We have recently presented experimental evidence of cysteine deficit, which functionally regulates both lowered levels of endogenous H2S and HH-induced neuropathological responses. In this review, we sought to understand the role of H2S and the transsulfuration pathway at HA.